2016
DOI: 10.1111/ilr.12038
|View full text |Cite
|
Sign up to set email alerts
|

Are Labor Inspections Protecting Workers' Rights? Adding the Evidence from Size-based Labor Regulations and Fines in Peru

Abstract: This paper analyzes how changes in the enforcement of labor regulations impact on the compliance rate in a context where the labor rules and the characteristics of the labor inspection system differ by firm size. In addition to the channels analyzed in the existing literature -the deterrence effect of labor inspections and the movement of displaced workers into the informal sector, this paper adds a margin of adjustment not analyzed before: firms can reduce their size to take advantage of lower penalties for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Among these services is the use of the “Planilla.” The Planilla is the formal register of labour relationships. Wage employees who are registered in the Planilla are entitled to several benefits according to the Peruvian law (Viollaz, ). In order to analyse whether internet adoption impacts positively on labour productivity through a formalization channel, I use an indicator for whether firm i uses the Planilla as an outcome variable.…”
Section: Resultsmentioning
confidence: 99%
“…Among these services is the use of the “Planilla.” The Planilla is the formal register of labour relationships. Wage employees who are registered in the Planilla are entitled to several benefits according to the Peruvian law (Viollaz, ). In order to analyse whether internet adoption impacts positively on labour productivity through a formalization channel, I use an indicator for whether firm i uses the Planilla as an outcome variable.…”
Section: Resultsmentioning
confidence: 99%
“…The Planilla is the formal register of labor relationships. Wage employees who are registered in the Planilla are entitled to several benefits according to the Peruvian law (Viollaz, 2017). In order to analyze whether internet adoption impacts positively on labor productivity through a formalization channel, I use as outcome variable an indicator for whether firm i uses the Planilla.…”
Section: Employment Conditionsmentioning
confidence: 99%
“…These studies use the variation in the enforcement of labor regulations rather than or in addition to changes in the regulation itself to identify effects on labor outcomes. Within country studies have concluded that higher enforcement of the labor law reduces firms' size and possibly productivity (Almeida and Carneiro 2009), decreases job creation and increases job destruction (Almeida and Poole 2017), increases the compliance with labor market regulations (Ronconi 2010;Almeida et al 2013) or does not have any effect on it (Bhorat et al 2012;Viollaz 2018), increases formal employment and nonemployment, reduces informal employment, leads to a fall in formal wages at the top of the wage distribution and to informal wage increases (Almeida and Carneiro 2012), and reduces deprovision of non-mandated benefits (Almeida et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%